Resignifying poetry in high school classrooms: The vision on poetry education of three reference teachers in Spain - Pardo Caicedo, Manuela; Munita, Felipe (Revista Complutense de Educación, 2021)
This study is framed within the teaching of literature, specifically in the field of poetic education. It examines the discourse of three high school teachers of language and literature, considered as reference instructors in their socio-educational context. The main objective has been to investigate and systematize their visions about the teaching of poetry in the classroom. For this purpose, this study follows a qualitative methodology, focused on a case study that uses the semi structured interview as its main data-collection technique. The data obtained were analyzed through emerging categories, both on theoretical discourse and on methodological discourse about poetic education. The results inform the importance that these teachers give to the personal experience of the reader, the socialization and collective construction of meanings, as well as to the selection of texts based on the didactic objectives and the students’ profile. The discussion of results reinforces the lines of continuity between the visions of this teachers and those of the current teaching of literature.
Keywords: teaching literatura; poetry; literary education; teachers